On a Set of Economic Support Measures for Companies Whose Products Have the Status of Telecommunication Equipment of Russian Origin - A. P. Isaev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
Economic support measures, including concessional lending to buyers of such products and reduction of customs duties on components not produced in the territory of the Russian Federation, should stimulate the development of the market for the consumption of domestic Telecom equipment in Russia. The digital transformation of Russia it is a matter of national security of country. Support of national culture, a single information and statistical industry center, reduction of retirement age and equipment with video cameras of children’s institutions, the movement of volunteers and the mechanism of “on-site inspections” of buyers of Telecom equipment market — is the basis of support for companies whose products have the status of telecommunications equipment of Russian origin.